2021
DOI: 10.1002/apj.2732
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of alternative refrigerants for R134a in automotive air conditioning system

Abstract: Aiming to explore environmentally friendly working fluids replace R134a for automotive air conditioning applications, seven potential pure refrigerants were analyzed first in terms of safety, environmental characteristics, and cycle performances. It was found that the pure refrigerants have some defects when applied individually. However, using the principle of complementary advantages, the mixtures employed in automotive air conditioning can make up for the shortcomings existing in the pure refrigerants. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the literature, studies on vehicle air conditioning have generally focused on improving driver comfort conditions, using different refrigerants, optimizing air conditioning elements and working conditions [4]. In addition to these studies, there are studies on refrigerants such as R-152a, R-430a, R-290, which can be an alternative to R-13a refrigerant in vehicle air conditioning systems [5][6][7][8][9][10][11]. Many studies have been conducted to determine the appropriate design of a bus air conditioner [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, studies on vehicle air conditioning have generally focused on improving driver comfort conditions, using different refrigerants, optimizing air conditioning elements and working conditions [4]. In addition to these studies, there are studies on refrigerants such as R-152a, R-430a, R-290, which can be an alternative to R-13a refrigerant in vehicle air conditioning systems [5][6][7][8][9][10][11]. Many studies have been conducted to determine the appropriate design of a bus air conditioner [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, because it is most similar to R134a, the Specific Compressor Displacement can be used with minimal system modification. Dai et al [5][6][7] constructed a simulation model for a vehicle air-conditioning system and analyzed the COP, heat per unit volume, pressure ratio, and discharge temperature for R134a, its alternative refrigerants, and mixed refrigerants. The results of this study revealed that R13I1/R152a and R13I1/R290 mixed refrigerants were superior to R134a in terms of the environment and performance.…”
Section: Introductionmentioning
confidence: 99%